Construction Of CIBEST Model as Measurement of Poverty and Welfare Indices From Islamic Perspective - Irfan Syauqi Beik; Laily Dwi Arsyianti (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2015)
One of the major challenges faced by most of the Islamic countries is poverty. This paper attempts to construct the concept of poverty and welfare standards based on Islamic perspective.The study tries to cover both material and spiritual dimensions. These standards are based on CIBEST Quadrant, which is divided into four quadrants: welfare quadrant (I), material poverty quadrant (II), spiritual poverty quadrant (III) and absolute poverty quadrant (IV). Determination of these quadrants is resulted from criteria and indicators of basic material needs and basic spiritual needs. By using household as unit of analysis, this study is able to developCIBEST Model comprising welfare index, material poverty index, spiritual poverty index, and absolute poverty index. Mathematical formula and illustration of the indices are also elaborated to strengthen the concept.DOI:10.15408/aiq.v7i1.1361